Genes and Proteomes Associated With Increased Mutation Frequency and Multidrug Resistance of Naturally Occurring Mismatch Repair-Deficient Salmonella Hypermutators - Sheng, Huanjing; Huang, Jinling; Han, Zhaoyu; Liu, Mi; Lü, Zexun; Zhang, Qian; Zhang, Jinlei; Yang, Jun; Cui, Shenghui; Yang, Baowei (Frontiers in Microbiology, 2020)
Emergence of antibiotic-resistant Salmonella through mutations led to mismatch-repair (MMR) deficiency represents potential hazard to public health. Here, four representative MMR deficient Salmonella hypermutator strains and Salmonella Typhimurium LT2 were used to comprehensively reveal the influence of MMR deficiency on antibiotic resistance among Salmonella. Our results indicated the mutation frequency ranged from 3.39×10–4 to 5.46×10–2 in the hypermutator. Mutation sites in MutS, MutL, MutT, and UvrD of the four hypermutators all located in the essential and core functional regions. Mutation frequency of the hypermutator was most highly correlated with the extent of mutation in MutS. Mutations in MMR genes (mutS, mutT, mutL, uvrD) were correlated with increased mutation in antibiotic resistance genes, the extent of antibiotic resistance was significantly correlated with the number of mutation sites in MutL and in ParC. The number of mutation sites in MMR genes and antibiotic resistance genes exhibited significant positive correlation with the number of antibiotics resisted and with expression levels of mutS, mutT and mutL. Compared to Salmonella Typhimurium LT2, a total of 137 differentially expressed and 110 specifically expressed proteins were identified in the four hypermutators. Functional enrichment analysis indicated the proteins significantly overexpressed in the hypermutators primarily associated with translation and stress response. Interaction network analysis revealed that the ribosome pathway might be a critical factor for high mutation frequency and multidrug resistance in MMR deficient Salmonella hypermutators. These results help elucidate the mutational dynamics that lead to hypermutation, antibiotic resistance, and activation of stress response pathways in Salmonella.